Acoustic pressure pipette aspiration method combined with finite element analysis for isotropic materials - Maghzinajafabadi, Mohammadali; Lamprecht, Raphael; Semmler, Marion; Sutor, Alexander (Applied Sciences, 2019)
A measurement setup combined with a numerical simulation by a linear finite element analysis is presented as a method to determine the elastic modulus of both artificial and real tissue as a function of frequency. At the end, the future goal is to develop and validate the method to measure the elastic modulus of in-vivo human vocal folds over the human phonation frequency range. In the present study, a miniaturized acoustic pressure pipette aspiration technique is developed to measure the material characteristics of an isotropic silicone specimen with similar characteristics as human vocal folds. In previous studies, friction and compression force effects of the pipette tip wall on the surface of the sample and the radius of the pipette were not investigated. Moreover, the large scale of the measurement setups made them impossible to use for clinical applications. Therefore, two different pipette sample cross-section boundary conditions and two different pipette radii were used. With the aim of ensuring reliable results, we tested our method with pipettes of two different radii on four silicone samples with different consistencies over a frequency range of 50-500 Hz. The simulation verified the measurement results in which the strong dependency of the elastic modulus on the excitation frequency, radius of the pipette, the pipette tip compression force and friction was revealed. By the simulation results, two different frequency dependent equations were developed for calculating elastic modulus of the silicone mixtures in the two cross-section boundary conditions. It was concluded that using a very small gap in between the pipette tip and the specimen can cancel the impact of the pipette tip force and friction which are the major cause of uncertainty. However, if a connection between the pipette and the surface is unpreventable, the contact force should be restricted to be absolutely zero.
CRIS-Team Scopus Importer:2019-09-27
Keywords: Elastic modulus; Laser vibrometry; Numerical simulation; Pipette aspiration; Pipette wall force; Poisson's ratio; Vocal folds; Young's modulus